Structural Biology Practical NMR Applications - Teng, Quincy; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2013)
Over the years since NMR was first applied to solve problems in structural biology, both NMR instrument hardware and methodology have been dramatically developed. This book offers a much-needed update to the 2005 first edition, and will be of critical importance to those who routinely use NMR to study various biological systems as well as a textbook. Thus, the book is organized with experimentalists in mind, whether they are instructors or students. For those who have minimal background in NMR structural biology, this book will provide fresh perspective and insight; those who are already well-versed in NMR research will find cutting edge updates and new information and methods that are useful to their research. Because understanding fundamental principles and concepts of NMR spectroscopy is essential for the application of NMR methods to research projects, the book begins with an introduction to basic NMR principles. Next, NMR instrumentation is discussed starting with hardware components. Topics include magnetic field homogeneity and stability, signal generation and detection, probe circuits, cryogenic probe, analog-to-digital conversion, and test equipment. A typical specification for a NMR spectrometer is also included in the chapter. There is also a chapter covering NMR sample preparation, a process that is often the bottleneck for the success of the NMR projects. Several routine strategies for preparing samples, especially for macromolecules as well as complexes are dealt with in detail.
Basic Principles of NMR -- Instrumentation -- NMR Sample Preparation -- Practical Aspects -- Multi-Dimensional Heteronuclear NMR Experiments -- Studies Of Small Biological Molecules -- Protein Structure Determination From NMR Data -- Protein Dynamics -- NMR-based Metabolomics.
Keywords: Medicine; Biotechnology; Biochemistry; Biomedicine; Molecular Medicine; Biomedicine general; Biophysics and Biological Physics; Biochemistry, general; Biotechnology